The relationship between plant-eating and hair evacuation in snow leopards (Panthera uncia). - Hiroto Yoshimura (PLoS ONE, 2020)
Although most felids have an exclusive carnivore diet, the presence of plant matter in scat has been reported among various species. This indicates that there may be an adaptive significance to the conservation of plant-eating behavior in felid evolution. Some studies have hypothesized that felids consume plants for self-medication or as a source of nutrition. In addition, it is thought that plant intake helps them to excrete hairballs, however, no scientific work has confirmed these effects. Thus, the objective of this study is to investigate the relationship between plant intake and hair evacuation in felid species. We selected snow leopards (Panthera uncia) as the study species because they have longer and denser hair than other felids. The behavior of 11 captive snow leopards was observed and scat samples from eight of them and two other captive individuals were analyzed. Snow leopards evacuate hair possibly by vomiting and excreting in scats. The frequency of plant-eating and vomiting and the amount of hair and plant in scat were evaluated. We found that the frequency of vomiting was much lower than the frequency of plant-eating. In addition, there was no significant relationship between the amount of plant matter contained in scats and the amount of hair in scats. Contrary to the common assumption, our results indicate that plant intake has little effect on hair evacuation in felid species.